2022
DOI: 10.3390/sym15010093
|View full text |Cite
|
Sign up to set email alerts
|

On a Certain Subclass of p-Valent Analytic Functions Involving q-Difference Operator

Abstract: This paper introduces and studies a new class of analytic p-valent functions in the open symmetric unit disc involving the Sălăgean-type q-difference operator. Furthermore, we present several interesting subordination results, coefficient inequalities, fractional q-calculus applications, and distortion theorems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…If the derivative and integral concepts in these models are replaced with q-and q, ω-analogs, new problems and new fields of study are created and solution methods are sought. Some recent works related to q-calculus include in [19,25,26,35,36,39] (also cited therein), and studies on q-calculus up to 2000 can be seen in [15]. Although the q, ω-derivative was defined in the 1950s, the q, ω-calculus subject is a newer field of study since the q, ω-inverse derivative (integral) was defined in 2009.…”
Section: Introductionmentioning
confidence: 99%
“…If the derivative and integral concepts in these models are replaced with q-and q, ω-analogs, new problems and new fields of study are created and solution methods are sought. Some recent works related to q-calculus include in [19,25,26,35,36,39] (also cited therein), and studies on q-calculus up to 2000 can be seen in [15]. Although the q, ω-derivative was defined in the 1950s, the q, ω-calculus subject is a newer field of study since the q, ω-inverse derivative (integral) was defined in 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the same idea, many authors have extensively studied the q-calculus operators (q-differential and q-integral operators) in GFT. A recent study on these operators acting on analytic functions can be found in [12][13][14][15][16][17][18][19]. For 0 < q < 1, Jackson [9,10] defined the q-differential operator, D q , of a function, ξ, as the following:…”
Section: Introductionmentioning
confidence: 99%